(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article reviews the new methods in the theory and practice of preventing ethnic confl icts. The author analyzes early warning and early response systems to the confl icts and their role in ensuring the stability and security in the society. Key words: ethnic confl ict, early warning, early response, conflictprevention.